The Effectiveness Of Three Step Interview Technique On Students Speaking Skill - Febrisa, Ratni; Sakti, Genta; Syafitri , Widya; Safitri, Loli (Indonesian Research Journal on Education, 2023)
The research was conducted because, the researcher is interested in seeing how effectiveness of three step interview technique on students peaking skill during speaking learning. The method in this research is descriptive quantitative research. The data obtained from the results of documentation and interviews with a teacher who used three step interview technique in teaching speaking. The research used saturated sampling because all populations is sampled. Based on the result of the research, it can be concluded that Three-Step Interview technique was effective used when teaching speaking. This can be seen from the result of the researcher interview with a teacher who used three step interview and supported by an average students result during learning speaking which reacjed 77,27 %. In other word, the effevtiveness of three step intervoew technique was in effective.